Ethnic identity dynamics in Komi-Perm and Russian students in the learning process - Dmitriy S. Kornienko1; Igor' V. Gaidamashko; Sergei L. Kandybovich (Rossijskij psihologičeskij žurnal., 2017)
Ethnic identity is a system of the individual’s representations and attitudes concerning his/her ethnic group. The learning process positively affects interethnic interaction and promotes the mutual acceptance of ethnic groups. The Komi-Perm people lose their ethnic identity because of the desire to belong to a wider or more attractive socio-ethnic group. The paper attempts the following: (a) to present the study of ethnic identity and ethnoaffiliative motives in Komi-Perm and Russian students; (b) to examine ethnic identity dynamics in Komi-Perm and Russian students in the learning process; (c) to analyze the joint effect of factors of ethnos, stage of training, and gender. Works of G. U. Soldatova, T. G. Stefanenko, and V. Yu. Khotinets in the field of ethnic identity provided the theoretical and methodological basis for this study. The participants comprised 273 junior and senior students. The “Types of Ethnic Identity” questionnaire (G. U. Soldatova, S. V. Ryzhova) was applied to examine the characteristics of ethnic identity. Statistical methods included comparative analysis, t-test, and variance analysis. The study findings suggest that negative characteristics of ethnic identity decrease in Komi-Perm and Russian students in the joint learning process. Gender differences in ethnopsychological characteristics were manifested in the fact that women had higher rates of a positive ethnic identity. The results are of applied value for forming positive interethnic relations and identity.